2016
DOI: 10.1016/j.xphs.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Soy Phosphatidylinositol–Containing Lipid Nanoparticle Prolongs the Plasma Survival and Hemostatic Efficacy of B-domain–Deleted Recombinant Canine Factor VIII in Hemophilia A Dogs

Abstract: Soy phosphatidylinositol (PI) containing lipid nanoparticles prolong plasma survival, improve hemostatic efficacy, and decrease immunogenicity of human B-domain deleted Factor VIII (BDD FVIII) in Hemophilia A (HA) mice. We hypothesize that PI associated BDD FVIII is more potent than the free protein, and using mathematical modeling, have projected that PI associated BDD FVIII could be used for once-weekly prophylactic dosing in patients. To facilitate translation to the clinic, comparative plasma survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The signal intensities from regions of interest were expressed as total photon flux (photons per second), which has been used widely in studies. 51 , 52 …”
Section: Methodsmentioning
confidence: 99%
“…The signal intensities from regions of interest were expressed as total photon flux (photons per second), which has been used widely in studies. 51 , 52 …”
Section: Methodsmentioning
confidence: 99%
“…Liposomes can encapsulate drugs for different medical purposes: thrombin inhibitors, able to exert an anticoagulant activity in case of arterial acute thrombosis [ 136 ], mRNA to encode erythropoietin, factor IX protein [ 137 ] and anti-factor VIII antibodies [ 138 , 139 ] for haemophilia treatment and Tmprss6 siRNA for thalassemia cure [ 140 ].…”
Section: Nanoparticle-based Therapymentioning
confidence: 99%
“…Moreover, joined researches represented the efficacy of using B-domain deleted (BDD)-rFVIII conjugated soy phosphatidylinositol lipidic nanoparticles in reducing inhibitory development and 1.5-fold extend and 1.4-fold increase in terminal half-life of BDD-rFVIII to 18 hours in mice clinical trials and dogs, respectively. Simultaneously, the immunogenicity assay has been evaluated in the presence of labeled anti IgG as well (59)(60)(61). Furthermore, in similar research in 2018, it has been demonstrated that subcutaneous administration of Lys-phosphatidylserine could extend the half-life to 1.6 fold by reducing the immunogenicity (62).…”
mentioning
confidence: 99%